Importancia de los fundamentos axiológicos en el aprendizaje significativo de los estudiantes del sexto y séptimo año de educación básica de la Unidad Educativa “Ana Páez” de la ciudad de Latacunga - Guanoluisa Tulpa, Myriam Vanessa (2015)
Currently the reality of societies characterized by a lack of values that influences the behavior of students is reflected in high rates of violence, intolerance, disrespect for self and others, turn on your School performance is why modern society demand that there individuals capable of having good habits so that they are not discriminated against in society and lead a decent life so this work is intended to improve the relationship between student and teacher or vice versa in order to inspire and convey how important values such as respect, responsibility, solidarity, democracy, and tolerance, to improve their living in their daily lives for which is necessary to raise awareness among parents that from a Home should educate their children with ethical and moral values so when they enter schools have no problem learning therefore research is conducted to sixth- and seventh year since it is considered that at this stage of development, Student thinking is becoming more independent and critical but this is where the teacher plays a key role as it is responsible to form with good principles and provide a significant learning in students.